(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotation. In the article, the norms of foliar application of the suspension prepared on the basis of urea fertilizers in the cotton variety “Andijan-35” grown in the conditions of typical gray soils of the Andijan region during the development periods of cotton, the effect on plant growth and development, cotton yield was determined.